ENT600 : VB bracelet / Wan Nur Nasuha Adila Mustaffa Amir, Nurul Shafizah Sham and Nor Zafirahani A.Razak - Mustaffa Amir, Wan Nur Nasuha Adila; Sham, Nurul Shafizah; A.Razak, Nor Zafirahani (2015)
The team is developing the VB bracelet which stands for Volleyball Bracelet. VB bracelet is a training bracelet that uses an sensors to measure the speed, elbow and wrist arc angle of a volleyball player's spiking skill. The bracelet save the data and provide feedback to enable the player to improve his/her spiking performance. Moreover, the VB bracelet can interfere with other player and rank the player's performance.